2002
DOI: 10.3904/kjim.2002.17.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Early dipyridamole stress myocardial SPECT to detect residual stenosis of infarct related artery : comparison with coronary angiography and fractional flow reserve

Abstract: BackgroundThe detection of residual stenosis of infarct related artery (IRA) at early stage after acute myocardial infarction (AMI) is crucial in clinical decision making for interventional revascularization. The aim of this study was to evaluate the relevancy of early dipyridamole stress myocardial SPECT to detect functionally and luminologically significant residual stenosis of IRA after AMI.MethodsTwenty five consecutive patients (M:F=19:6, age: 56±13yrs) with AMI underwent SPECT and coronary angiography wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…An FFR Յ0.78 was found to provide optimal discriminatory power for detecting reversibility on SPECT or MCE, with no significant loss in sensitivity to detect ischemia in large infarct sizes. Debate has arisen regarding the accuracy of FFR after MI, as FFR determination depends upon the assumption that vasodilator-mediated hyperemia achieves a state of Samady et al June 6, 2006June 6, :2187 Fractional Flow Reserve Early After MI minimal and constant coronary resistance (8,11,12). DeBruyne et al (7) showed that FFR identified inducible ischemia on SPECT in patients 20 Ϯ 27 days (range 6 to 570 days) after MI, specifically excluding patients with MIs within six days of FFR assessment.…”
Section: Discussionmentioning
confidence: 99%
“…An FFR Յ0.78 was found to provide optimal discriminatory power for detecting reversibility on SPECT or MCE, with no significant loss in sensitivity to detect ischemia in large infarct sizes. Debate has arisen regarding the accuracy of FFR after MI, as FFR determination depends upon the assumption that vasodilator-mediated hyperemia achieves a state of Samady et al June 6, 2006June 6, :2187 Fractional Flow Reserve Early After MI minimal and constant coronary resistance (8,11,12). DeBruyne et al (7) showed that FFR identified inducible ischemia on SPECT in patients 20 Ϯ 27 days (range 6 to 570 days) after MI, specifically excluding patients with MIs within six days of FFR assessment.…”
Section: Discussionmentioning
confidence: 99%
“…What appeared consistent across several studies, was that values between 0.76 and 0.80 showed sub-optimal specificity for predicting non-invasive test results and these values were, therefore, labelled as being in the 'grey zone', whereby clinician judgement would be required to decide whether a lesion was ischaemia-producing, based on the broader clinical picture. [17][18][19][20][21][22][23][24][25][26][27] Despite the obvious minor variability in the measurement and predictive performance of FFR in clinical studies, it is clear from these studies that using an FFR cut-off value of ≤0.75 has a good chance of identifying ischaemia in the vessel being examined.…”
Section: Ffr Cut-off Valuesmentioning
confidence: 99%
“…1,14,15,[17][18][19][20][21][22][23][24][25][26][27][34][35][36][37][38] The adenosine doses that had diagnostic ability to identify ischaemiaproducing lesions against non-invasive tests were 140 μg/kg/min and up to maximum of 40-60 μg for intravenous administration of adenosine and intracoronary adenosine, respectively (see Table 1). …”
Section: Routes and Doses Of Adenosine Administrationmentioning
confidence: 99%
“…Several independent studies have since demonstrated that FFR values between 0.67 and 0.75 accurately predict positive myocardial perfusion scintigraphy, exercise treadmill and stress echo results (see Table 1). [17][18][19][20][21][22][23][24][25][26][27] Note that, as with all in vivo tests, variability was seen across the studies. One value for FFR did not consistently predict the same thing in different populations; nor did it consistently predict response again the same test.…”
Section: Ffr Cut-off Valuesmentioning
confidence: 99%
“…During the initial FFR validation work against non-invasive ischaemia tests, two routes of administration were used to establish cut-off values -intravenous adenosine and intracoronary adenosine. 1,14,15,[17][18][19][20][21][22][23][24][25][26][27][34][35][36][37][38] The adenosine doses that had diagnostic ability to identify ischaemiaproducing lesions against non-invasive tests were 140 μg/kg/min and up to maximum of 40-60 μg for intravenous administration of adenosine and intracoronary adenosine, respectively (see Table 1).…”
Section: Routes and Doses Of Adenosine Administrationmentioning
confidence: 99%